Local Potential Eco-Friendly Corrosion Bio-inhibitors for Iron Material in Karang Jahe Marine - Puji Winarti; Putut Marwoto; Sunyoto Eko Nugroho (School of Postgraduate Studies, Diponegoro Univer, 2026)
The seawater of Karang Jahe, Rembang Regency, provides a highly saline, chloride-rich environment that accelerates the corrosion of iron materials widely used in local fishing activities. Although synthetic corrosion inhibitors are effective, their long-term application raises ecological concerns due to toxicity. Plant-based extracts offer a biodegradable and environmentally safer alternative. However, studies investigating locally sourced coastal plants under natural seawater conditions remain limited. This study is novel in that it evaluates locally sourced teak leaf (Tectona grandis L.f.) and tengar bark (Ceriops tagal) extracts from the Karang Jahe coastal area as eco-friendly corrosion inhibitors in natural seawater media. Immersion experiments showed a consistent decrease in corrosion rates with increasing inhibitor concentrations. After 20 days of immersion at 20 ppm, inhibition efficiencies of 90.75% for teak leaf extract and 93.49% for tengar bark extract were achieved, demonstrating strong and sustained corrosion protection under realistic marine conditions. Peak efficiencies were observed after 10 days, suggesting effective early stage adsorption of the inhibitor molecules on the iron surface. Overall, tengar bark extract demonstrated stronger corrosion protection. This finding highlights its potential as a locally sourced and environmentally friendly inhibitor for marine applications.